Love's subtle magic an Indian Islamic literary tradition, 1379-1545 - Behl, Aditya, 1966-2009.; Doniger, Wendy (New York ; Oxford : Oxford University Press, 2013)
The encounter between Muslim and Hindu remains one of the defining issues of South Asian society today. This encounter began as early as the 8th century, and the first Muslim kingdom in India would be established at the end of the 12th century. This powerful kingdom, the Sultanate of Delhi, eventually reduced to vassalage almost every independent kingdom on the subcontinent. In 'Love's Subtle Magic', a remarkable and deeply original book, Aditya Behl uses a little-understood genre of Sufi literature to paint an entirely new picture of the evolution of Indian culture during the earliest period of Muslim domination.
Studying the Sultanate period -- Inaugurating Hindavi -- Creating a new genre : the Candayan -- Oceans and stories : the Mirigavati -- The landscape of paradise and the embodied city : the Padmavat. Part 1 -- The conquest of Chittaur : the Padmavat. Part 2 -- Bodies that signify : the Madhumalati. Part 1 -- The seasons of Madhumalati's separation : the Madhumalati. Part 2 -- Hierarchies of response -- Epilogue: The story of stories.
Includes bibliographical references and index.
Includes index.
Master record variable field(s) change: 072 - OCLC control number change
Keywords: Sufi literature, Hindi -- History and criticism; India -- Civilization; Civilization; Sufi literature, Hindi; India; LITERARY CRITICISM / Asian / Indic; E-books.; E-reference.; Criticism, interpretation, etc